Modified Minimally Invasive Bunnell Suture Surgery with Channel-assisted Minimally Invasive Reconstruction Device for Treating Achilles Tendon Rupture - Li, Chao; Li, Fu-chun (Zeitschrift für Orthopädie und Unfallchirurgie, 2024)
The aim of this study was to improve the process of microincision and endoscopic surgery for the treatment of Achilles tendon (AT) rupture using the modified minimally invasive Bunnell suture (MIBS) technique.From December 2019 to December 2021, 20 patients with AT rupture who visited the First Affiliated Hospital of Harbin Medical University (Harbin, China) underwent MIBS surgery.A total of 20 patients were included, of whom 18 (90.0%) were male and 2 (10.0%) were female. The mean age of the patients was 37.75 ± 9.94 years. In terms of the site of the AT, two (10.0%) had surgery on their left AT. The mean duration of surgery was 23.00 ± 2.47 minutes, and the mean bleeding volume was 5.00 ± 1.12 mL. All 20 patients (100%) showed complete incisional healing (stage I healing) and normal functional recovery (3–6 months postoperatively). There were no cases of abnormal functional recovery or postoperative recurrence within the 3–6 month follow-up period. The Achilles tendon Total Rupture Score (ATRS) significantly improved post-surgery (83.6 ± 5.59) compared to pretreatment (0.3 ± 0.92, p < 0.0001), indicating successful patient recovery.After the modified MIBS surgical process, the operation steps were simplified, the surgical difficulty was reduced, and the surgical trauma was alleviated, resulting in good postoperative recovery and patient satisfaction with the outcome. Therefore, the MIBS surgery has high promotability.
Keywords: Achilles tendon rupture; tunnel-assisted suture system; minimally invasive surgery